Nachfrageorientiertes Nutzungszyklusmanagement - Bizer, Kilian; Ewen, Christoph; Knieling, Jörg; Othengrafen, Frank; Stieß, Immanuel (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
Policy and practice perspective